2016
DOI: 10.1371/journal.pone.0146562
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Knock-In Pigs Carrying Oct4-tdTomato Reporter through CRISPR/Cas9-Mediated Genome Engineering

Abstract: The porcine pluripotent cells that can generate germline chimeras have not been developed. The Oct4 promoter-based fluorescent reporter system, which can be used to monitor pluripotency, is an important tool to generate authentic porcine pluripotent cells. In this study, we established a porcine Oct4 reporter system, wherein the endogenous Oct4 promoter directly controls red fluorescent protein (RFP). 2A-tdTomato sequence was inserted to replace the stop codon of the porcine Oct4 gene by homogenous recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Genetic analysis fully confirmed the clonal origin of the monkeys generated by SCNT. This study demonstrated that cloning of non-human primates is feasible by SCNT using fetal somatic cells, which could be efficiently modified by genetic editing and screening in vitro (Gao et al, 2017;Lai et al, 2016;Rogers, 2016). Such cloning allows the production of genetically uniform monkeys as animal models for basic research in primate biology and for studying human disease mechanisms and therapeutic treatments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Genetic analysis fully confirmed the clonal origin of the monkeys generated by SCNT. This study demonstrated that cloning of non-human primates is feasible by SCNT using fetal somatic cells, which could be efficiently modified by genetic editing and screening in vitro (Gao et al, 2017;Lai et al, 2016;Rogers, 2016). Such cloning allows the production of genetically uniform monkeys as animal models for basic research in primate biology and for studying human disease mechanisms and therapeutic treatments.…”
Section: Discussionmentioning
confidence: 93%
“…Monkey neonates generated using fetal fibroblasts were healthy, whereas those generated using adult cumulus cells survived only briefly after birth. Since fetal fibroblasts could be genetically modified efficiently in vitro and properly screened for precise gene editing (Gao et al, 2017;Lai et al, 2016;Rogers, 2016) prior to SCNT, our results pave the way for the generation of genetically uniform monkey models for basic research and biomedical applications.…”
Section: Introductionmentioning
confidence: 88%
“…In this form, due to the same transcriptional gene activation, it allows easy quantification or detection of the expression of genes of interest. Reporter cell lines can be used to study specific genes and monitor cell differentiation in PSC; therefore, these lines have been used in a wide variety of studies Lai et al, 2016;Zhang et al, 2016). It should be noted that genetic modification of stem/progenitor cells can alter their biological properties and differentiation characteristics.…”
Section: Challengesmentioning
confidence: 99%
“…CRISPR/Cas9 targeting in cell lines followed by SCNT can also reduce the need for breeding as it has been exemplified by generation of PARK2 -/-PINK1 -/-double mutant for modeling Parkinson"s disease [68]. Multiple knock-in strategies have also been developed in the pig, one interesting example of which is Oct4-tdTomato pig transgenic reporter line produced using SCNT, where expression of tdTomato was present in pluripotent cells of the embryos [69]. Zygote injection of large knock-in constructs with Cas9 and sgRNA in the pigs resulted in insertion of human albumin cDNA into the pig albumin locus with all founder animals expressing at least some human albumin [70] and defined mutations were introduced into the pig Sox10 gene using singlestranded DNA oligos [71].…”
Section: Crispr/cas9 In Animal Modelsmentioning
confidence: 99%